Preliminary Evidence of a Horizontal Transfer of Paramutation Phenomenon at the pl1 Gene in Maize (Zea mays L.) - Roberto Pilu; Martina Ghidoli; Alessia Follador; Alessandro Passera; Paola Casati; Ervane Laure Cheyep Dinzeu; Elena Cassani; Michela Landoni (Plants)
Paramutation, a specific epigenetic phenomenon first identified in Zea mays by Alexander Brink in the 1950s, has since been observed in different plant and animal species. What sets paramutation apart from other gene silencing processes is its ability for one silenced allele (referred to as paramutagenic) to silence another allele (paramutable) in trans. The resultant silenced allele (paramutated) remains stable across generations, even after separating from the paramutagenic allele, and acquires paramutagenic properties itself. This hereditary behavior facilitates the rapid dissemination of specific gene expression patterns or phenotypes within populations, disrupting the Hardy–Weinberg equilibrium even without other evolutionary pressures. Despite extensive research, the molecular mechanisms underlying paramutation are still not fully understood, although numerous studies suggest the involvement of RNA-mediated changes in DNA methylation and in the chromatin structure of silenced genes. In this paper, we report preliminary evidence regarding horizontal paramutation transfer at the pl1 (purple plant1) regulatory gene involved in the accumulation of anthocyanin in several plant tissues such as tassel, kernel, and cob. A paramutated pl1′ allele arose spontaneously in a pl1 population, and in this study, we found evidence of silencing events spatially associated in the field, suggesting a possible horizontal transfer of silencing among nearby plants.